Chromosomal Abnormalities of Interest in Turner Syndrome: An Update - Ibarra-Ramírez, Marisol; Campos-Acevedo, Luis Daniel; Martínez de Villarreal, Laura E. (Journal of Pediatric Genetics, 2023)
Turner syndrome (TS) is caused by the total or partial loss of the second sex chromosome; it occurs in 1 every 2,500–3,000 live births. The clinical phenotype is highly variable and includes short stature and gonadal dysgenesis. In 1959, the chromosomal origin of the syndrome was recognized; patients had 45 chromosomes with a single X chromosome. TS presents numerical and structural abnormalities in the sex chromosomes, interestingly only 40% have a 45, X karyotype. The rest of the chromosomal abnormalities include mosaics, deletions of the short and long arms of the X chromosome, rings, and isochromosomes. Despite multiple studies to establish a relationship between the clinical characteristics and the different chromosomal variants in TS, a clear association cannot yet be established. Currently, different mechanisms involved in the phenotype have been explored. This review focuses to analyze the different chromosomal abnormalities and phenotypes in TS and discusses the possible mechanisms that lead to these abnormalities.
Keywords: Turner syndrome; X chromosome; X chromosome monosomy